Speaking Difficulties in Presenting Physics Experiments: A Survey Study - Alviana, Gina; Al Fath, Kilaz Munjin Mu’afi; Wahyunengsih, Wahyunengsih (DIKSI: Jurnal Kajian Pendidikan dan Sosial, 2025)
Speaking difficulties in English-medium physics experiment presentations remain an underexplored issue, as they involve linguistic, psychological, and discipline-specific factors. This study aims to identify the types and levels of speaking difficulties experienced by physics students during experiment presentations. A descriptive quantitative survey design was employed involving 61 respondents, consisting of 56 physics students and five physics teachers or lecturers. Data were collected using a validated questionnaire measuring several domains of speaking difficulty, including pronunciation, fluency and delivery, vocabulary and grammar, interaction and question-and-answer sessions, and content organisation. The data were analysed using descriptive statistics. The results indicate that pronunciation, fluency, and delivery constitute the most dominant challenges (M = 3.10), followed by interaction and Q&A (M = 3.05) and vocabulary grammar issues (M = 3.04), while content organisation is the least problematic aspect (M = 2.90). Speaking anxiety is at a moderate level (M = 3.20), mainly characterised by physical symptoms and fear of negative evaluation. Furthermore, 87% of respondents reported insufficient oral proficiency despite having conceptual understanding of physics content. These findings highlight the need for structured speaking training in physics courses, particularly focusing on technical vocabulary mastery, guided oral explanations, and simulated Q&A practice to support clearer and more confident scientific communication.